2016
DOI: 10.1002/2016wr019186
|View full text |Cite
|
Sign up to set email alerts
|

Landscape controls on spatiotemporal discharge variability in a boreal catchment

Abstract: Improving the understanding of how stream flow dynamics are influenced by landscape characteristics, such as soils, vegetation and terrain, is a central endeavor of catchment hydrology. Here we investigate how spatial variability in stream flow is related to landscape characteristics using specific discharge time series from 14 partly nested subcatchments in the Krycklan basin (0.12 – 68 km2). Multivariate principal component analyses combined with univariate analyses showed that while variability in landscape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
83
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 75 publications
(100 reference statements)
6
83
0
Order By: Relevance
“…We used temporally constant lapse rates, but they may vary in different seasons, latitudes, and orographic influences (Stone and Carlson, 1979;Sevruk and Mieglitz, 2002). Altitude effects are negligible for the gently sloping Krycklan site (Karlsen et al, 2016).…”
Section: Model Input and Test Datamentioning
confidence: 99%
“…We used temporally constant lapse rates, but they may vary in different seasons, latitudes, and orographic influences (Stone and Carlson, 1979;Sevruk and Mieglitz, 2002). Altitude effects are negligible for the gently sloping Krycklan site (Karlsen et al, 2016).…”
Section: Model Input and Test Datamentioning
confidence: 99%
“…Studies of watershed topography on hydrological processes often include topics such as specific discharge (Karlsen et al, 2016), spatial baseflow distribution (Shope, 2016), transit time (McGuire et al, 2005;McGuire and McDonnell, 2006), and hydrological connectivity (Jencso and McGlynn, 2011). These studies were often based on a short period of data (< 5 years), limiting our ability to draw general conclusions on how topography affects hydrological processes.…”
Section: Q LI Et Al: Topography Significantly Influencing Low Flowsmentioning
confidence: 99%
“…Our study identified that TWI and wetland area were not significantly related to flow variables, indicating that these factors had a limited role in the selected flow variables in our region. This may be because the watersheds in this area need 265 to overcome a soil moisture storage threshold prior to releasing water (Karlsen et al, 2016). In summary, our 5 selected TIs significantly represent low flow characteristics of the watersheds in the southern interior of British Columbia, Canada, which is characterized by a snow-dominated hydrological regime.…”
mentioning
confidence: 94%
“…Studies of watershed topography on hydrological processes often include topics such as specific discharge (Karlsen et al, 2016), spatial baseflow distribution (Shope, 2016), transit time (McGuire and McDonnell, 2006;McGuire et al, 2005), and hydrological connectivity (Jencso and McGlynn, 2011). 65…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation